Exploration in utilization of Lablab purpureus (L.) Sweet in Central Lombok Regency as a support in food security based on local germplasm management and conservation - Kurniasih Sukenti; Nur Indah Julisaniah; Sukiman Sukiman; Rina Kurnianingsih (Jurnal Biologi Tropis, 2022)
Komak (generally assumed and known as Lablab purpureus (L.) Sweet) is one of the important food commodities in Fabaceae family, especially for people on Lombok Island, West Nusa Tenggara. Komak bean is also one of the common plants which is widely grown on Lombok Island in general. The objects of this research are to explore the various uses on some morphological variants of komak plant in Central Lombok Regency as one of komak production area on Lombok Island, including its potency of development strategies. This descriptive exploratory research was conducted in Central Lombok Regency as one of the important areas for komak population, supported by interviews, participatory observation and documentation. Snowball sampling method was applied in informant selection. Data were analyzed based on the calculation of Reported Use (RU) and Index of Cultural Significance (ICS). As the results, there are about 10 (ten) utilizations of komak plant reported by the community: as food, yard plants, land boundaries, economic plants, natural fertilizers, ecological functions (soil cover/erosion prevention), animal feed, seasonal indicators, ritual, and socio-cultural functions. Dissemination of information about processing technology and utilization of komak plant are still needed in order to support the optimalization of the management and utilization of this commodity as one of potential legumes that has a strategic role in realizing national food security.